2021
DOI: 10.3390/microorganisms9081614
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Novel Family IV and VIII Esterases from a Compost Metagenomic Library

Abstract: Two novel esterase genes, est8L and est13L, were isolated and identified from a compost metagenomic library. The encoded Est8L and Est13L had molecular masses of 33,181 and 44,913 Da consisting of 314 and 411 amino acids, respectively, without signal peptides. Est8L showed the highest identity (32.9%) to a hyper-thermophilic carboxylesterase AFEST from Archaeoglobus fulgidus compared to other esterases reported and was classified to be a novel member of family IV esterases with conserved regions such as HGGG, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 74 publications
0
11
0
Order By: Relevance
“…Comparisons of their enzymatic properties with Lip54q are shown in Table 5. The results in Table 5 show that the optimum pH of Lip54q was higher than those for EstCS1 (Park et al, 2020a), Est56 (Lu and Daniel, 2021), Est1 (Lu et al, 2019), and EstCS3 (Park et al, 2020b) and was equal to those for Est2 (Lu et al, 2019) and Est8L (Park et al, 2021), but lower than that of Est13L (Park et al, 2021). In addition, the optimum temperature for Lip54q was similar to those of most esterases but significantly lower than those for Est1 and Est2 (Lu et al, 2019).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Comparisons of their enzymatic properties with Lip54q are shown in Table 5. The results in Table 5 show that the optimum pH of Lip54q was higher than those for EstCS1 (Park et al, 2020a), Est56 (Lu and Daniel, 2021), Est1 (Lu et al, 2019), and EstCS3 (Park et al, 2020b) and was equal to those for Est2 (Lu et al, 2019) and Est8L (Park et al, 2021), but lower than that of Est13L (Park et al, 2021). In addition, the optimum temperature for Lip54q was similar to those of most esterases but significantly lower than those for Est1 and Est2 (Lu et al, 2019).…”
Section: Discussionmentioning
confidence: 92%
“…In recent years, several lipid hydrolases with unique enzymatic characteristics have been identified from composting habitats (Lu et al, 2019;Park et al, 2020aPark et al, ,b, 2021Lu and Daniel, 2021). Although these enzymes belong to different ester hydrolase families, including family IV (Park et al, 2020a(Park et al, , 2021Lu and Daniel, 2021), family V (Lu et al, 2019), and family VIII (Lu et al, 2019;Park et al, 2020bPark et al, , 2021, the optimal substrates for these enzymes are p-nitrophenyl ester substrates with short carbon chains. Therefore, these enzymes are esterases rather than lipases.…”
Section: Discussionmentioning
confidence: 99%
“…Chauhan [ 56 ] and Dhanjal, Chopra [ 57 ] reviewed several novel enzymes discovered using a metagenomic approach, including lipases and esterases obtained from different environmental samples. Recently, a cold-active esterase PMGL3 was obtained from the metagenomic DNA library of Siberian permafrost, and other lipase genes have also been isolated and identified from various metagenomic libraries [ 36 , 58 , 59 ]. These studies showed that metagenomics is an effective technique for identifying, extracting, and discovering novel lipolytic enzymes.…”
Section: Approaches For Isolation Of Genes Encoding Cold-active Lipas...mentioning
confidence: 99%
“…They were mixed, digested with a restriction enzyme, cloned with plasmid pUC19, and 18 positive subclones were obtained [19]. By sequencing, nine different lipolytic enzymes were identified, and some of them were reported [19,23,24]. In this study, a positive clone YH-E15 was selected for further study.…”
Section: A Positive Esterase Clone From the Compost Metagenomic Librarymentioning
confidence: 99%
“…Compost has been selected as an object of metagenomic study because it contains various useful enzymes, such as endoglucanase, xylanase, and esterase [20][21][22]. We selected the compost metagenome and reported the properties of some lipolytic enzymes obtained from the compost metagenomic library, such as Est2K, Est7K, Est8L, and Est13L [19,23,24]. Recently, a family IV esterase from another compost metagenome was reported, and it showed organic solvent stability [25].…”
Section: Introductionmentioning
confidence: 99%